Meeting preschool screen time recommendations: which parental strategies matter? - Fitzpatrick, Caroline; Cristini, Emma; Bernard, Jonathan Y.; Garon-Carrier, Gabrielle (Frontiers in Psychology, 2023)
For full guidelines please refer to Author Guidelines Background: High levels of screen use by preschoolers may contribute to adverse health and developmental outcomes. Little is known about which parental strategies may be protective against intensive screen use by children. Our aim is to estimate whether parent strategies for mediating child screen time including restrictive and instructive mediation and social coviewing, predict preschooler adherence to the screen time recommendation of ≤1 hour/day during the COVID-19 pandemic. We also examine if parent restrictive mediation interacts with child temperament characteristics.Methods: Our sample is composed of 315 Canadian parents of preschoolers surveyed during the COVID-19 pandemic. Parents provided measures of child adherence to screen time guidelines at ages 3.5 (baseline) and 4.5 years. Parents also reported how often they used restrictive and instructional mediation, and social coviewing to manage their child's screen use. Control variables include child sex and temperament (effortful control, negative affectivity, extraversion), educational attainment, and parenting stress at age 3.5.A logistic regression revealed that parental restrictiveness was associated with a 4 time increase in the odds of adherence to screen time guidelines, OR=4.07 (95% CI [1.70-13.03]). Parental social coviewing decreased the chances of adherence by 80% (OR=.20,). Furthermore, children not meeting recommendation at 3.5 were 98% less likely to respect the recommendation 1 year later (OR=.02, 95% CI [.01-.07]). Results were adjusted for child sex, temperament, baseline screen time, and parent education and stress The interaction between the restriction mediation and child temperament on later screen time was not significant.Our results indicate that some parental strategies may be more effective than others for managing preschooler screen time. Parent use of restrictive mediation was most likely to forecast child adherence to later screen time recommendations. The present results may contribute to the 2 This is a provisional file, not the final typeset article development of targeted family-based interventions designed to promote healthy development from a young age.